Nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material as well as preparation method and application thereof

By preparing nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composites, the problem of large particle size and poor dispersion of transition metal-based catalysts is solved, and efficient catalytic modification of magnesium-based solid hydrogen storage materials is achieved, improving hydrogen absorption and discharge performance and cycle stability.

CN120515468APending Publication Date: 2025-08-22QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)

Patent Information

Application Number
CN202510666296.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

The existing transition metal-based catalysts have large particle sizes, poor dispersion, easy to agglomerate, and poor catalytic performance, which affects the kinetic and thermodynamic properties of magnesium-based solid hydrogen storage materials.

Method used

A nitrogen-doped carbon-coated nickel-manganese-based bimetal nanosphere composite was prepared. Through the solvothermal method and calcining process, NiMnO@NC composite material was formed with small particle size and good dispersion. Combined with the synergistic catalytic action of nickel-manganese bimetal and the surface defects of the nitrogen-doped carbon layer, the stability and activity of the catalyst were improved.

Benefits of technology

The hydrogen absorption and release performance of magnesium-based solid hydrogen storage materials is significantly improved, the initial hydrogen release temperature is reduced, the cycle stability and catalytic activity are enhanced, and the catalytic modification effect of MgH2 is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005415221900000011
    Figure HDA0005415221900000011
  • Figure HDA0005415221900000012
    Figure HDA0005415221900000012
  • Figure HDA0005415221900000021
    Figure HDA0005415221900000021
Patent Text Reader

Abstract

The invention provides a nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material as well as a preparation method and application thereof. The preparation method of the composite material comprises the following steps: fully dissolving a nickel source and a manganese source in isopropanol, adding glycerol, uniformly mixing, and carrying out solvothermal reaction, centrifugation, drying and calcination to obtain nickel-manganese-based nanospheres; and fully dispersing the nickel-manganese-based nanospheres in an alkaline aqueous solution, adding a dopamine source, reacting, centrifuging, washing, drying and calcining to obtain the nickel-manganese-based nanospheres. The preparation method is simple, the product structure and performance are controllable, and the obtained composite material is a nickel-manganese-based bimetallic nanosphere with the surface coated with a nitrogen-doped carbon layer and has the advantages of high specific surface area, small and uniform particle size and good dispersity; the composite material disclosed by the invention is applied to the field of magnesium-based solid hydrogen storage, nickel-manganese bimetals play a synergistic catalytic effect, and the composite material shows excellent magnesium-based solid hydrogen storage catalytic modification performance in combination with surface defects and high cycle stability brought by a nitrogen-doped carbon layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of composite material preparation, and specifically relates to a nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material, a preparation method and an application thereof. Background Art

[0002] Solid-state hydrogen storage technology offers advantages such as good safety, low energy consumption, and high energy density, providing a highly promising solution to storage issues in hydrogen economy systems. Magnesium-based solid-state hydrogen storage materials (MgH2) have attracted widespread attention due to their low cost, abundant reserves, and good reversibility. However, in practical applications, they still face the dual challenges of slow kinetics and excessive thermodynamic stability. Introducing a catalyst through ball milling can improve the hydrogen absorption and desorption rate of MgH2 while reducing the operating temperature. This modification method is currently the most commonly used due to its high efficiency and low cost.

[0003] Transition metal-based catalysts have multiple valence states and strong electronic control capabilities, which can significantly reduce the hydrogen absorption and desorption energy barrier of MgH2. In addition, compared with single transition metal catalysts, bimetallic catalysts exhibit superior catalytic performance due to the synergistic effect between their components. However, existing transition metal-based catalysts have large particle size and poor dispersion, resulting in fewer active sites for reaction and are more prone to agglomeration, which affects their catalytic performance and cyclic stability. Therefore, the rational design of morphology and structure is also the key to achieving good catalytic effects.

[0004] Carbon materials not only act as catalysts but also as excellent dispersants, effectively inhibiting the agglomeration and growth of MgH₂ particles during the recycling process. Furthermore, carbon materials facilitate uniform dispersion of the catalyst on the MgH₂ surface during ball milling and enhance the stability of transition metal-based catalysts. Heteroatom doping is one method for enhancing the performance of carbon materials, further improving their catalytic performance towards MgH₂.

[0005] Chinese patent document CN119524882A discloses a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-loaded Fe-TM bimetallic alloy catalyst, its preparation method and application. The catalyst of this invention is a sulfur self-doped mesoporous carbon-loaded Fe-TM solid solution alloy material formed by calcining high-sulfur petroleum coke under the activation of potassium ferrate in an inert atmosphere and reducing and calcining in a hydrogen atmosphere. The high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-loaded Fe-TM bimetallic alloy catalyst provided by this invention can reduce the peak dehydrogenation temperature of magnesium-based materials by 80 to 110K. The raw materials selected for this invention are industrial by-products, which have good cost-effectiveness. However, industrial by-products usually have large purity differences between batches, making it difficult to ensure the S doping ratio, affecting controllability and stability. In addition, the catalyst formation process of this patent relies on high-temperature ball milling and high-temperature reduction, which is relatively complex and energy-intensive, and the catalytic performance needs to be further improved.

[0006] Therefore, it is of great significance to develop a heteroatom-doped carbon and transition metal composite nanosphere catalyst with simple preparation method, controllable, good dispersion, small and uniform particle size to significantly improve its magnesium-based solid-state hydrogen storage catalytic modification performance. Summary of the Invention

[0007] In response to the shortcomings of the existing technology, the present invention provides a nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material and its preparation method and application, in order to solve the problems of large particle size, poor dispersibility, easy agglomeration and growth, and poor catalytic performance of current transition metal-based catalysts. The preparation method of the present invention is simple, and the product structure and performance are controllable. The obtained composite material is a nickel-manganese-based bimetallic nanosphere coated with a nitrogen-doped carbon layer on the surface, which has a high specific surface area, a small and uniform particle size, and good dispersibility; the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material of the present invention is applied to the field of magnesium-based solid-state hydrogen storage. The nickel-manganese bimetallic exerts a synergistic catalytic effect, combined with the surface defects and high cycle stability brought by the nitrogen-doped carbon layer, so that the composite material exhibits excellent magnesium-based solid-state hydrogen storage catalytic modification performance.

[0008] The technical solutions of the present invention are as follows:

[0009] A nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere (NiMnO@NC) composite material is provided. The composite material is a nickel-manganese-based bimetallic nanosphere with a nitrogen-doped carbon layer coated on its surface.

[0010] Preferably according to the present invention, the microscopic morphology of the composite material is a nanosphere structure with a particle size of 150-200 nm.

[0011] The preparation method of the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material comprises the following steps:

[0012] (1) fully dissolving the nickel source and the manganese source in isopropanol, adding glycerol, mixing uniformly, subjecting to solvent thermal reaction, centrifuging, drying, and calcining to obtain nickel-manganese-based nanospheres;

[0013] (2) The nickel-manganese-based nanospheres are fully dispersed in an alkaline aqueous solution, a dopamine source is added, and the mixture is reacted, centrifuged, washed, dried, and calcined to obtain a nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material.

[0014] According to the present invention, preferably, in step (1), the nickel source is one of nickel sulfate, nickel nitrate, nickel chloride or nickel acetate.

[0015] According to the present invention, preferably, in step (1), the manganese source is one of manganese sulfate, manganese chloride, manganese nitrate or manganese acetate.

[0016] According to the preferred embodiment of the present invention, in step (1), the molar ratio of the manganese source to the nickel source is 1: (1 to 5), preferably 1: 2. The ratio between the manganese source and the nickel source will have a significant impact on the catalytic activity of the composite material.

[0017] According to the preferred embodiment of the present invention, in step (1), the volume ratio of the molar amount of the nickel source to the isopropanol is 0.01 to 1 mmol / mL, preferably 0.0125 mmol / mL. Adding too little isopropanol will affect the dispersibility of the nickel source and the manganese source, ultimately resulting in an incomplete spherical structure. Adding too much isopropanol will lead to a decrease in the viscosity of the solution, affecting the structural guidance effect of glycerol, and ultimately affecting the formation of the nanosphere structure.

[0018] According to the present invention, preferably, in step (1), the volume ratio of glycerol to isopropanol is 0.1-1:1, preferably 0.4:1. Glycerol acts as a structure-directing agent, regulating the nucleation and growth rate under solvent thermal conditions, thereby forming a nanosphere structure. If too little is added, the spherical structure will be incomplete. If too much is added, the particles will adhere and accumulate, ultimately leading to the formation of a non-spherical structure.

[0019] According to the preferred embodiment of the present invention, in step (1), the temperature of the solvothermal reaction is 120-200°C; and the time of the solvothermal reaction is 4-10 hours. Appropriate reaction conditions are conducive to the production of nanosphere materials with uniform size and good crystallinity. If the reaction time and temperature are too low, the material nucleation will be incomplete and the crystallinity will be reduced. Conversely, the material grains will be too large, the particles will agglomerate, and the structure will collapse.

[0020] According to a preferred embodiment of the present invention, in step (1), the calcination temperature is 400-500°C; the calcination atmosphere is air; and the calcination time is 1-4 hours. Calcination can remove water of crystallization in the material and increase crystallinity. Calcination in air can also decompose residual glycerol and isopropyl alcohol, thereby increasing the purity of the material.

[0021] According to the preferred embodiment of the present invention, in step (2), the pH of the alkaline aqueous solution is 8-9; the alkaline aqueous solution is a tris(hydroxymethyl)aminomethane hydrochloride) aqueous solution or an ammonia solution. Dopamine can undergo spontaneous oxidative polymerization in an alkaline solution, and a solution pH that is too high or too low will affect the formation of polydopamine.

[0022] According to the preferred embodiment of the present invention, in step (2), the volume ratio of the mass of the nickel-manganese-based nanospheres to the alkaline aqueous solution is 1:0.5-5 mg / mL.

[0023] According to the present invention, preferably, in step (2), the dopamine source is dopamine or dopamine hydrochloride. Dopamine is unstable and easily oxidized in the air, while dopamine hydrochloride is relatively stable.

[0024] According to the preferred embodiment of the present invention, in step (2), the mass ratio of nickel-manganese-based nanospheres to dopamine source is 1: (0.5-2), preferably 1: 1. The ratio of nickel-manganese-based nanospheres to dopamine source affects the thickness of the coated carbon layer and the degree of metal reduction, thereby affecting the catalytic performance of the material.

[0025] According to the present invention, preferably, in step (2), the reaction temperature is room temperature, the reaction time is 12 to 24 hours, and the reaction is carried out under stirring. If the reaction time is too short, the dopamine polymerization is insufficient, which affects the coating effect.

[0026] According to a preferred embodiment of the present invention, in step (2), the calcination temperature is 400-500°C; the calcination atmosphere is an inert gas; preferably, the inert gas is nitrogen or argon; and the calcination time is 1-4 hours. Calcination can carbonize the polydopamine to form a nitrogen-doped carbon layer. Polydopamine is also reducing and can reduce metal oxides during the calcination process, ultimately affecting the catalytic performance of the material.

[0027] Application of the above nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material in magnesium hydride hydrogen storage.

[0028] According to a preferred embodiment of the present invention, the application method comprises the steps of: uniformly mixing the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material with magnesium hydride by ball milling to obtain a modified magnesium hydride material for magnesium hydride hydrogen storage.

[0029] Preferably, the mass ratio of the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material to magnesium hydride is 1:7-22; the ball milling speed is 350-650 r / min, and the ball milling time is 2-5 h.

[0030] The technical features and beneficial effects of the present invention are as follows:

[0031] (1) The present invention first fully dissolves the nickel source and manganese source in isopropanol and glycerol. During the solvent thermal reaction, the structure of the glycerol is guided to form a spherical structure, and finally nickel-manganese-based nanospheres are obtained by calcination. The nickel-manganese-based nanospheres and the dopamine source are then fully dispersed in an alkaline aqueous solution and magnetically stirred. The alkaline environment is conducive to the self-polymerization of dopamine. The generated polydopamine has high viscosity and is easily precipitated and coated on the surface of the nickel-manganese-based nanospheres. The polydopamine is then carbonized by calcination to obtain a NiMnO@NC composite material. The preparation method of the NiMnO@NC composite material of the present invention is simple, has mild reaction conditions, is highly efficient, has few reaction steps, low energy consumption, and is low in cost. A nickel-manganese-based bimetallic nanosphere composite material with nitrogen-doped carbon coating can be prepared by a simple one-time solvent thermal reaction and calcination, and the product structure and performance are controllable.

[0032] (2) The NiMnO@NC composite material obtained in the present invention is a nickel-manganese-based bimetallic nanosphere coated with a nitrogen-doped carbon layer on the surface. It has the characteristics of small size (150-200 nm), high specific surface area, uniform particle size, and good dispersibility, which is beneficial to improving the dispersibility and cycle stability of the composite material in hydrogen storage materials and is beneficial to improving the catalytic performance.

[0033] (3) In the NiMnO@NC composite material obtained by the present invention, the nickel-manganese bimetallic material exerts a synergistic catalytic effect. The spherical morphology and nanoscale size of the composite material can increase the specific surface area of ​​the material and provide more active sites for the hydrogen absorption / desorption reaction of MgH2. The nitrogen-doped carbon layer improves the defect level, electronegativity and dispersibility of the catalyst after ball milling on the surface of the composite material, which can accelerate the adsorption and dissociation of hydrogen molecules on the surface of the composite material. At the same time, the presence of the carbon layer can inhibit the agglomeration and growth of MgH2, thereby improving the cycle performance of MgH2. The nickel-manganese bimetallic material of the present invention is composed of metal Ni and MnO. In the field of magnesium-based solid-state hydrogen storage, metal Ni can form Mg2Ni / Mg2NiH4 phase with Mg, which can act as a "hydrogen pump" during the hydrogen absorption / desorption process and effectively reduce the reaction energy barrier. Therefore, compared with oxidized Ni, elemental Ni has better catalytic performance. At the same time, there is a good synergistic catalytic effect between MnO and Ni, which can further enhance the "hydrogen pump effect" of Mg2Ni / Mg2NiH4 in the hydrogen storage process. Therefore, NiMnO@NC enhances its catalytic effect on MgH2 hydrogen storage through synergistic effects. The preparation method of the present invention, as a whole, combines the various steps and conditions to produce the NiMnO@NC composite material with the structure and performance of the present invention. The NiMnO@NC composite material of the present invention has applications in magnesium-based solid-state hydrogen storage. Due to the synergistic effect of the nickel-manganese bimetallic and the nitrogen-doped carbon layer coating it, combined with the nano-spherical structure, it enhances the catalytic absorption and desorption of MgH2, demonstrating excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 XRD pattern of the NiMnO@NC composite material prepared in Example 1;

[0035] Figure 2 SEM and energy spectrum of the NiMnO@NC composite material prepared in Example 1;

[0036] Figure 3 This is the XPS graph of the NiMnO@NC composite material prepared in Example 1;

[0037] Figure 4 This is a temperature-dependent hydrogen release curve of NiMnO@NC modified magnesium hydride prepared in Example 1;

[0038] Figure 5This is the isothermal hydrogen release curve of NiMnO@NC modified magnesium hydride prepared in Example 1;

[0039] Figure 6 This is the isothermal hydrogen absorption curve of NiMnO@NC modified magnesium hydride prepared in Example 1;

[0040] Figure 7 This is the isothermal hydrogen release curve of NiMnO@NC modified magnesium hydride prepared in Example 3;

[0041] Figure 8 This is the isothermal hydrogen absorption curve of NiMnO@NC modified magnesium hydride prepared in Example 4;

[0042] Figure 9 This is the isothermal hydrogen release curve of NiMnO@NC modified magnesium hydride prepared in Example 5;

[0043] Figure 10 This is the isothermal hydrogen absorption curve of NiMnO@NC modified magnesium hydride prepared in Example 6;

[0044] Figure 11 The temperature-dependent hydrogen release curve of magnesium hydride in Comparative Example 1 is shown;

[0045] Figure 12 is the isothermal hydrogen release curve of magnesium hydride in Comparative Example 1;

[0046] Figure 13 This is the isothermal hydrogen absorption curve of magnesium hydride in Comparative Example 1. DETAILED DESCRIPTION

[0047] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.

[0048] Meanwhile, the experimental methods described in the following examples, unless otherwise specified, are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial channels.

[0049] Example 1

[0050] A method for preparing a NiMnO@NC composite material comprises the following steps:

[0051] (1) 0.5 mmol nickel nitrate hexahydrate and 0.25 mmol manganese chloride tetrahydrate were dissolved in 40 mL isopropanol and magnetically stirred for 30 min. Subsequently, 16 ml glycerol was dispersed in the above solution and ultrasonicated for 30 min. The solution was solvothermally reacted at 180 °C for 10 h. After the reaction, the precipitate was collected by centrifugation and dried, and calcined at 400 °C in air for 2 h to obtain nickel-manganese-based nanospheres.

[0052] (2) 0.05 g of nickel-manganese-based nanospheres were dispersed in 50 ml of tris(hydroxymethylaminomethane) hydrochloride aqueous solution with a pH of 8.5. After ultrasonication for 1 h, 0.05 g of dopamine hydrochloride was added and magnetic stirring was carried out at room temperature for 24 h. After the end, the precipitate was collected by centrifugation, washed, and dried to obtain a polydopamine-coated nickel-manganese-based bimetallic nanosphere composite material.

[0053] (3) The composite material obtained in the previous step was calcined at 500 °C for 2 h in a nitrogen atmosphere to obtain a NiMnO@NC composite material.

[0054] Figure 1 The XRD pattern of the NiMnO@NC composite material prepared in this example shows that the diffraction peaks of the composite material are consistent with the standard cards of Ni and MnO (PDF#04-0850 and PDF#07-0230), and there are no diffraction peaks of other phases, which proves that the composite material synthesized by this method has high purity.

[0055] Figure 2 The SEM and energy spectrum images of the NiMnO@NC composite prepared in this example show the composite's nanosphere-like structure, approximately 150-200 nm in size. The energy spectrum also reveals good dispersion of carbon, nickel, and manganese, demonstrating the synthesis of uniform, carbon-coated nickel-manganese bimetallic nanospheres.

[0056] Figure 3 This is the XPS spectrum of the NiMnO@NC composite material prepared in this example. The figure clearly shows the characteristic peaks of carbon, nitrogen, oxygen, nickel, and manganese elements, proving that a nitrogen-doped carbon-coated nickel-manganese-based bimetallic composite material has been synthesized.

[0057] The application of the above-mentioned NiMnO@NC composite material in magnesium hydride hydrogen storage is as follows:

[0058] 0.05g of NiMnO@NC composite material was ball-milled with 0.45g of commercial magnesium hydride at room temperature at a speed of 500 rpm for 4 hours. The resulting composite sample was then subjected to variable temperature hydrogen desorption, isothermal hydrogen desorption, and isothermal hydrogen absorption performance tests. The variable temperature hydrogen desorption test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 450°C at a rate of 5°C / min. The amount of hydrogen released during this process was measured. The isothermal hydrogen desorption performance test was as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 275°C at a rate of 5°C / min. The sample was then held at 275°C for 30 minutes. The amount of hydrogen released during this period was measured and plotted as an isothermal hydrogen desorption curve. The isothermal hydrogen absorption test conditions are as follows: 150 mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was raised from room temperature to 100 °C at a heating rate of 5 °C / min. A hydrogen pressure of 4 MPa was provided at 100 °C and kept warm for 1 h. The amount of hydrogen absorbed during the 100 °C holding process was measured.

[0059] The temperature-varying hydrogen release test shows that the NiMnO@NC catalytically modified magnesium hydride prepared in this embodiment has a lower initial hydrogen release temperature. Figure 4 As shown in the figure, after modification with NiMnO@NC (MgH2-1NiMnO@NC), the initial dehydrogenation temperature is reduced to 225°C, and dehydrogenation can be completed at 315°C. The isothermal dehydrogenation test shows that the magnesium hydride catalytically modified with NiMnO@NC prepared in this embodiment can significantly increase the dehydrogenation rate. Figure 5 As shown in the figure, after modification with NiMnO@NC (MgH2-1NiMnO@NC), the hydrogen release process was almost completed in only 7 minutes at 275°C, and the amount of hydrogen released reached 5.98 wt.%. The isothermal hydrogen absorption test showed that the magnesium hydride catalytically modified with NiMnO@NC prepared in this example can significantly improve the hydrogen absorption rate. Figure 6 As shown, after modification with NiMnO@NC (MgH2-1NiMnO@NC), the hydrogen absorption process was almost completed in only 5.5 min at 100 °C, and the hydrogen absorption capacity reached 5.46 wt.%.

[0060] Example 2

[0061] A method for preparing a NiMnO@NC composite material comprises the following steps:

[0062] (1) 0.25 mmol nickel nitrate hexahydrate and 0.25 mmol manganese chloride tetrahydrate were dissolved in 40 mL isopropanol and magnetically stirred for 30 min. Subsequently, 16 ml glycerol was dispersed in the above solution and ultrasonicated for 30 min. The solution was solvothermally reacted at 180 °C for 10 h. After the reaction, the precipitate was collected by centrifugation and dried, and calcined at 400 °C in air for 2 h to obtain nickel-manganese-based nanospheres.

[0063] (2) 0.05 g of nickel-manganese-based nanospheres were dispersed in 50 ml of tris(hydroxymethylaminomethane) hydrochloride aqueous solution with a pH of 8.5. After ultrasonication for 1 h, 0.05 g of dopamine hydrochloride was added and magnetic stirring was carried out at room temperature for 24 h. After the end, the precipitate was collected by centrifugation, washed, and dried to obtain a polydopamine-coated nickel-manganese-based bimetallic nanosphere composite material.

[0064] (3) The composite material obtained in the previous step was calcined at 500 °C for 2 h in a nitrogen atmosphere to obtain a NiMnO@NC composite material.

[0065] The application of the above-mentioned NiMnO@NC composite material in magnesium hydride hydrogen storage is as follows:

[0066] 0.05g NiMnO@NC composite material was ball-milled with 0.45g commercial magnesium hydride at room temperature, with a rotation speed of 500r / min and a ball-milling time of 4h. The obtained composite sample was subjected to variable temperature hydrogen desorption, isothermal hydrogen desorption and isothermal hydrogen absorption performance tests. The variable temperature hydrogen desorption test conditions are as follows: 150mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was increased from room temperature to 450℃ at a heating rate of 5℃ / min, and the amount of hydrogen released during this process was measured. The isothermal hydrogen desorption performance test was as follows: 150mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was increased from room temperature to 275℃ at a heating rate of 5℃ / min, and kept at 275℃ for 30min. The amount of hydrogen released during the holding process at 275℃ was measured and drawn into an isothermal hydrogen desorption curve. The isothermal hydrogen absorption test conditions are as follows: 150mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was increased from room temperature to 100℃ at a heating rate of 5℃ / min, and kept at 100℃

[0067] Provide 4 MPa of hydrogen pressure and keep warm for 1 hour, and measure the amount of hydrogen absorbed during the holding process at 100°C.

[0068] After the variable temperature hydrogen desorption test, the magnesium hydride catalytically modified by NiMnO@NC prepared in this embodiment has a lower initial hydrogen desorption temperature, but the modification effect is worse than that of Example 1. After modification with NiMnO@NC (MgH2-2NiMnO@NC), the initial hydrogen desorption temperature is reduced to 233°C, and hydrogen desorption can be completed at 324°C. After the isothermal hydrogen desorption test, the magnesium hydride catalytically modified by NiMnO@NC prepared in this embodiment can increase the hydrogen desorption rate, but the modification effect is worse than that of Example 1. After modification with NiMnO@NC (MgH2-2NiMnO@NC), 5.44wt.% of hydrogen can be released within 7 minutes at 275°C, and hydrogen desorption is completed in 11 minutes. After the isothermal hydrogen absorption test, the magnesium hydride catalytically modified by NiMnO@NC prepared in this embodiment can increase the hydrogen absorption rate. After modification with NiMnO@NC (MgH2-2NiMnO@NC), 4.47 wt.% of hydrogen can be absorbed within 5.5 min at 100 °C, and the hydrogen absorption is completed within 40 min.

[0069] Example 3

[0070] A method for preparing a NiMnO@NC composite material comprises the following steps:

[0071] (1) 0.25 mmol nickel chloride hexahydrate and 0.25 mmol manganese chloride tetrahydrate were dissolved in 40 mL isopropanol and magnetically stirred for 30 min. Subsequently, 16 ml glycerol was dispersed in the above solution and ultrasonicated for 30 min. The solution was subjected to solvothermal reaction at 180 °C for 8 h. After the reaction, the precipitate was collected by centrifugation and dried, and calcined at 400 °C in air for 2 h to obtain nickel-manganese-based nanospheres.

[0072] (2) 0.05 g of nickel-manganese-based nanospheres were dispersed in 50 ml of tris(hydroxymethyl)aminomethane hydrochloride aqueous solution with a pH of 9. After ultrasonication for 1 h, 0.05 g of dopamine hydrochloride was added and magnetic stirring was carried out at room temperature for 16 h. After the end, the precipitate was collected by centrifugation, washed, and dried to obtain a polydopamine-coated nickel-manganese-based bimetallic nanosphere composite material.

[0073] (3) The composite material obtained in the previous step was calcined at 450 °C in a nitrogen atmosphere for 2 h to obtain a NiMnO@NC composite material.

[0074] The application of the above-mentioned NiMnO@NC composite material in magnesium hydride hydrogen storage is as follows:

[0075] 0.035g of NiMnO@NC composite material was ball-milled with 0.465g of commercial magnesium hydride at room temperature at a speed of 500 rpm for 4 hours. The resulting composite sample was then subjected to variable temperature hydrogen desorption, isothermal hydrogen desorption, and isothermal hydrogen absorption tests. The variable temperature hydrogen desorption test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 450°C at a rate of 5°C / min. The amount of hydrogen released during this process was measured. The isothermal hydrogen desorption test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 275°C at a rate of 5°C / min. The sample was then held at 275°C for 30 minutes. The amount of hydrogen released during this period was measured and plotted as an isothermal hydrogen desorption curve. The isothermal hydrogen absorption test conditions are as follows: 150 mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was raised from room temperature to 100 °C at a heating rate of 5 °C / min. A hydrogen pressure of 4 MPa was provided at 100 °C and kept warm for 1 h. The amount of hydrogen absorbed during the 100 °C holding process was measured.

[0076] After the variable temperature hydrogen desorption test, the magnesium hydride modified by NiMnO@NC catalysis prepared in this embodiment has a lower initial hydrogen desorption temperature, but the modification effect is worse than that of Example 1. After modification with NiMnO@NC (MgH2-3NiMnO@NC), the initial hydrogen desorption temperature is reduced to 231°C, and hydrogen desorption can be completed at 320°C. After the isothermal hydrogen desorption test, the magnesium hydride modified by NiMnO@NC catalysis prepared in this embodiment can increase the hydrogen desorption rate, but the modification effect is worse than that of Example 1. Figure 7 As shown, after modification with NiMnO@NC (MgH2-3NiMnO@NC), 5.57 wt.% hydrogen was released within 7 minutes at 275°C, with complete hydrogen release in 9 minutes. Isothermal hydrogen absorption testing demonstrates that the NiMnO@NC-catalytically modified magnesium hydride prepared in this example can enhance hydrogen absorption. After modification with NiMnO@NC (MgH2-3NiMnO@NC), 4.63 wt.% hydrogen was absorbed within 5.5 minutes at 100°C, with complete hydrogen absorption taking 38 minutes.

[0077] Example 4

[0078] A method for preparing a NiMnO@NC composite material comprises the following steps:

[0079] (1) 0.5 mmol nickel nitrate hexahydrate and 0.25 mmol manganese nitrate tetrahydrate were dissolved in 40 mL isopropanol and magnetically stirred for 30 min. Then 16 ml glycerol was dispersed in the above solution and ultrasonicated for 30 min. The solution was solvothermally reacted at 160 °C for 10 h. After the reaction, the precipitate was collected by centrifugation and dried, and calcined at 500 °C in air for 2.5 h to obtain nickel-manganese-based nanospheres.

[0080] (2) 0.05 g of nickel-manganese-based nanospheres were dispersed in 50 ml of tris(hydroxymethyl)aminomethane hydrochloride aqueous solution with a pH of 9. After ultrasonication for 1 h, 0.1 g of dopamine hydrochloride was added and magnetic stirring was carried out at room temperature for 16 h. After the end, the precipitate was collected by centrifugation, washed, and dried to obtain a polydopamine-coated nickel-manganese-based bimetallic nanosphere composite material.

[0081] (3) The composite material obtained in the previous step was calcined at 450 °C in a nitrogen atmosphere for 2 h to obtain a NiMnO@NC composite material.

[0082] The application of the above-mentioned NiMnO@NC composite material in magnesium hydride hydrogen storage is as follows:

[0083] 0.035g of NiMnO@NC composite material was ball-milled with 0.465g of commercial magnesium hydride at room temperature at a speed of 500 rpm for 4 hours. The resulting composite sample was then subjected to variable temperature hydrogen desorption, isothermal hydrogen desorption, and isothermal hydrogen absorption tests. The variable temperature hydrogen desorption test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 450°C at a rate of 5°C / min. The amount of hydrogen released during this process was measured. The isothermal hydrogen desorption test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 275°C at a rate of 5°C / min. The sample was then held at 275°C for 30 minutes. The amount of hydrogen released during this period was measured and plotted as an isothermal hydrogen desorption curve. The isothermal hydrogen absorption test conditions are as follows: 150 mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was raised from room temperature to 100 °C at a heating rate of 5 °C / min. A hydrogen pressure of 4 MPa was provided at 100 °C and kept warm for 1 h. The amount of hydrogen absorbed during the 100 °C holding process was measured.

[0084] After the variable temperature hydrogen desorption test, the initial hydrogen desorption temperature of the NiMnO@NC catalytically modified magnesium hydride prepared in this embodiment was lowered, but the modification effect was worse than that of Example 1. After modification with NiMnO@NC (MgH2-4NiMnO@NC), the initial hydrogen desorption temperature was reduced to 238°C, and hydrogen desorption could be completed at 326°C. After the isothermal hydrogen desorption test, the NiMnO@NC catalytically modified magnesium hydride prepared in this embodiment can increase the hydrogen desorption rate, but the modification effect was worse than that of Example 1. After modification with NiMnO@NC (MgH2-4NiMnO@NC), 5.25wt.% of hydrogen can be released within 7 minutes at 275°C, and hydrogen desorption is completed in 10 minutes. After the isothermal hydrogen absorption test, the NiMnO@NC catalytically modified magnesium hydride prepared in this embodiment can significantly increase the hydrogen absorption rate, but the modification effect is worse than that of Example 1. As Figure 8As shown, after modification with NiMnO@NC (MgH2-4NiMnO@NC), 4.32 wt.% of hydrogen can be absorbed within 5.5 min at 100 °C, and the hydrogen absorption is completed in 42 min.

[0085] Example 5

[0086] A method for preparing a NiMnO@NC composite material comprises the following steps:

[0087] (1) 0.5 mmol nickel chloride hexahydrate and 0.25 mmol manganese nitrate tetrahydrate were dissolved in 40 mL isopropanol and magnetically stirred for 30 min. Subsequently, 16 ml glycerol was dispersed in the above solution and ultrasonicated for 30 min. The solution was solvothermally reacted at 200 °C for 10 h. After the reaction, the precipitate was collected by centrifugation and dried, and calcined at 450 °C in air for 2 h to obtain nickel-manganese-based nanospheres.

[0088] (2) 0.05 g of nickel-manganese-based nanospheres were dispersed in 50 ml of tris(hydroxymethylaminomethane) hydrochloride aqueous solution with a pH of 8.5. After ultrasonication for 1 h, 0.05 g of dopamine hydrochloride was added and magnetic stirring was carried out at room temperature for 20 h. After the end, the precipitate was collected by centrifugation, washed, and dried to obtain a polydopamine-coated nickel-manganese-based bimetallic nanosphere composite material.

[0089] (3) The composite material obtained in the previous step was calcined at 500 °C in a nitrogen atmosphere for 2.5 h to obtain a NiMnO@NC composite material.

[0090] The application of the above-mentioned NiMnO@NC composite material in magnesium hydride hydrogen storage is as follows:

[0091] 0.025g of NiMnO@NC composite material was ball-milled with 0.475g of commercial magnesium hydride at room temperature at a speed of 500 rpm for 4 hours. The resulting composite sample was then subjected to variable temperature hydrogen desorption, isothermal hydrogen desorption, and isothermal hydrogen absorption performance tests. The variable temperature hydrogen desorption test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 450°C at a rate of 5°C / min. The amount of hydrogen released during this process was measured. The isothermal hydrogen desorption performance test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 275°C at a rate of 5°C / min. The sample was then held at 275°C for 30 minutes. The amount of hydrogen released during the 275°C holding period was measured and plotted as an isothermal hydrogen desorption curve. The isothermal hydrogen absorption test conditions are as follows: 150 mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was raised from room temperature to 100 °C at a heating rate of 5 °C / min. A hydrogen pressure of 4 MPa was provided at 100 °C and kept warm for 1 h. The amount of hydrogen absorbed during the 100 °C holding process was measured.

[0092] After the variable temperature hydrogen desorption test, the magnesium hydride catalytically modified by NiMnO@NC prepared in this embodiment has a lower initial hydrogen desorption temperature, but the modification effect is worse than that of Example 1. After modification by NiMnO@NC (MgH2-5NiMnO@NC), the initial hydrogen desorption temperature is reduced to 245°C, and hydrogen desorption can be completed at 331°C. After the isothermal hydrogen desorption test, the magnesium hydride catalytically modified by NiMnO@NC prepared in this embodiment can increase the hydrogen desorption rate, but the modification effect is worse than that of Example 1. Figure 9 As shown, after modification with NiMnO@NC (MgH2-5NiMnO@NC), 4.11 wt.% hydrogen was released within 7 minutes at 275°C, with complete hydrogen release taking 12 minutes. Isothermal hydrogen absorption tests show that the magnesium hydride catalytically modified with NiMnO@NC prepared in this example can increase the hydrogen absorption rate, but the effect is less than that of Example 1. After modification with NiMnO@NC (MgH2-5NiMnO@NC), 3.88 wt.% hydrogen was absorbed within 5.5 minutes at 100°C, with complete hydrogen absorption taking 46 minutes.

[0093] Example 6

[0094] A method for preparing a NiMnO@NC composite material comprises the following steps:

[0095] (1) 0.5 mmol nickel nitrate hexahydrate and 0.25 mmol manganese chloride tetrahydrate were dissolved in 40 mL isopropanol and magnetically stirred for 30 min. Subsequently, 16 ml glycerol was dispersed in the above solution and ultrasonicated for 30 min. The solution was solvothermally reacted at 180 °C for 10 h. After the reaction, the precipitate was collected by centrifugation and dried, and calcined at 400 °C in air for 2 h to obtain nickel-manganese-based nanospheres.

[0096] (2) 0.05 g of nickel-manganese-based nanospheres were dispersed in 50 ml of tris(hydroxymethylaminomethane) hydrochloride aqueous solution with a pH of 8.5. After ultrasonication for 1 h, 0.05 g of dopamine hydrochloride was added and magnetic stirring was carried out at room temperature for 24 h. After the end, the precipitate was collected by centrifugation, washed, and dried to obtain a polydopamine-coated nickel-manganese-based bimetallic nanosphere composite material.

[0097] (3) The composite material obtained in the previous step was calcined at 500 °C for 2 h in a nitrogen atmosphere to obtain a NiMnO@NC composite material.

[0098] The application of the above-mentioned NiMnO@NC composite material in magnesium hydride hydrogen storage is as follows:

[0099] 0.025g of NiMnO@NC composite material was ball-milled with 0.475g of commercial magnesium hydride at room temperature at a speed of 500 rpm for 4 hours. The resulting composite sample was then subjected to variable temperature hydrogen desorption, isothermal hydrogen desorption, and isothermal hydrogen absorption performance tests. The variable temperature hydrogen desorption test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 450°C at a rate of 5°C / min. The amount of hydrogen released during this process was measured. The isothermal hydrogen desorption performance test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 275°C at a rate of 5°C / min. The sample was then held at 275°C for 30 minutes. The amount of hydrogen released during the 275°C holding period was measured and plotted as an isothermal hydrogen desorption curve. The isothermal hydrogen absorption test conditions are as follows: 150 mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was raised from room temperature to 100 °C at a heating rate of 5 °C / min. A hydrogen pressure of 4 MPa was provided at 100 °C and kept warm for 1 h. The amount of hydrogen absorbed during the 100 °C holding process was measured.

[0100] After the variable temperature hydrogen desorption test, the initial hydrogen desorption temperature of the NiMnO@NC catalytically modified magnesium hydride prepared in this embodiment is lowered, but the modification effect is worse than that of Example 1. After modification with NiMnO@NC (MgH2-6NiMnO@NC), the initial hydrogen desorption temperature is reduced to 248°C, and hydrogen desorption can be completed at 336°C. After the isothermal hydrogen desorption test, the NiMnO@NC catalytically modified magnesium hydride prepared in this embodiment can increase the hydrogen desorption rate, but the modification effect is worse than that of Example 1. After modification with NiMnO@NC (MgH2-6NiMnO@NC), 3.96wt.% of hydrogen can be released within 7 minutes at 275°C, and hydrogen desorption is completed in 15 minutes. After the isothermal hydrogen absorption test, the NiMnO@NC catalytically modified magnesium hydride prepared in this embodiment can increase the hydrogen absorption rate, but the modification effect is worse than that of Example 1. As Figure 10 As shown, after modification with NiMnO@NC (MgH2-6NiMnO@NC), 3.30 wt.% hydrogen can be absorbed within 5.5 min at 100 °C, and hydrogen absorption is completed in 49 min.

[0101] Example 7

[0102] A method for preparing a NiMnO@NC composite material comprises the following steps:

[0103] (1) 1 mmol nickel nitrate hexahydrate and 0.25 mmol manganese chloride tetrahydrate were dissolved in 40 mL isopropanol and magnetically stirred for 30 min. Subsequently, 16 ml glycerol was dispersed in the above solution and ultrasonicated for 30 min. The solution was solvothermally reacted at 180 °C for 10 h. After the reaction, the precipitate was collected by centrifugation and dried, and calcined at 400 °C in air for 2 h to obtain nickel-manganese-based nanospheres.

[0104] (2) 0.05 g of nickel-manganese-based nanospheres were dispersed in 50 ml of tris(hydroxymethylaminomethane) hydrochloride aqueous solution with a pH of 8.5. After ultrasonication for 1 h, 0.05 g of dopamine hydrochloride was added and magnetic stirring was carried out at room temperature for 24 h. After the end, the precipitate was collected by centrifugation, washed, and dried to obtain a polydopamine-coated nickel-manganese-based bimetallic nanosphere composite material.

[0105] (3) The composite material obtained in the previous step was calcined at 500 °C for 2 h in a nitrogen atmosphere to obtain a NiMnO@NC composite material.

[0106] The application of the above-mentioned NiMnO@NC composite material in magnesium hydride hydrogen storage is as follows:

[0107] 0.05g of NiMnO@NC composite material was ball-milled with 0.45g of commercial magnesium hydride at room temperature at a speed of 500 rpm for 4 hours. The resulting composite sample was then subjected to variable temperature hydrogen desorption, isothermal hydrogen desorption, and isothermal hydrogen absorption performance tests. The variable temperature hydrogen desorption test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 450°C at a rate of 5°C / min. The amount of hydrogen released during this process was measured. The isothermal hydrogen desorption performance test was as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 275°C at a rate of 5°C / min. The sample was then held at 275°C for 30 minutes. The amount of hydrogen released during this period was measured and plotted as an isothermal hydrogen desorption curve. The isothermal hydrogen absorption test conditions are as follows: 150 mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was raised from room temperature to 100 °C at a heating rate of 5 °C / min. A hydrogen pressure of 4 MPa was provided at 100 °C and kept warm for 1 h. The amount of hydrogen absorbed during the 100 °C holding process was measured.

[0108] After the variable temperature hydrogen desorption test, the magnesium hydride catalytically modified with NiMnO@NC prepared in this example has a lower initial hydrogen desorption temperature, but the modification effect is worse than that of Example 1. After modification with NiMnO@NC (MgH2-7NiMnO@NC), the initial hydrogen desorption temperature is reduced to 255°C, and hydrogen desorption can be completed at 347°C. After the isothermal hydrogen desorption test, the magnesium hydride catalytically modified with NiMnO@NC prepared in this example can increase the hydrogen desorption rate, but the modification effect is worse than that of Example 1. After modification with NiMnO@NC (MgH2-7NiMnO@NC), 3.32wt.% of hydrogen can be released within 7 minutes at 275°C, and hydrogen desorption is completed in 17 minutes. After the isothermal hydrogen absorption test, the magnesium hydride catalytically modified with NiMnO@NC prepared in this example can increase the hydrogen absorption rate, but the modification effect is worse than that of Example 1. After modification with NiMnO@NC (MgH2-6NiMnO@NC), 2.89 wt.% of hydrogen can be absorbed within 5.5 min at 100 °C, and hydrogen absorption is completed in 57 min.

[0109] Comparative Example 1

[0110] 0.5g of commercial magnesium hydride was ball-milled at room temperature at a speed of 500 rpm for 4 hours. The resulting sample was then subjected to variable temperature hydrogen desorption, isothermal hydrogen desorption, and isothermal hydrogen absorption performance tests. The variable temperature hydrogen desorption test conditions were as follows: 150mg of ball-milled MgH2 was transferred to a hydrogen storage tester and heated from room temperature to 450°C at a rate of 5°C / min. The amount of hydrogen released during this process was measured. The isothermal hydrogen desorption performance test was as follows: 150mg of ball-milled MgH2 was transferred to a hydrogen storage tester and heated from room temperature to 275°C at a rate of 5°C / min. The temperature was maintained at 275°C for 30 minutes. The amount of hydrogen released during this period was measured and plotted as an isothermal hydrogen desorption curve. The isothermal hydrogen absorption test conditions are as follows: 150 mg of ball-milled MgH2 was transferred to the hydrogen storage tester, and the temperature was raised from room temperature to 100°C at a heating rate of 5°C / min. A hydrogen pressure of 4 MPa was provided at 100°C and kept warm for 1 h. The amount of hydrogen absorbed during the 100°C holding process was measured.

[0111] The temperature-dependent hydrogen release test showed that the initial hydrogen release temperature of the ball-milled MgH2 without adding a catalyst was higher. Figure 11 As shown in the figure, the initial hydrogen desorption temperature of ball-milled MgH2 (MgH2) is 355°C and the desorption is completed at 424°C. According to the isothermal desorption test, the ball-milled MgH2 without adding catalyst can hardly desorb hydrogen at 275°C. Figure 12 As shown in Figure 2, ball-milled MgH2 (MgH2) can only release 0.8 wt.% of hydrogen in 60 minutes at 275°C. According to the isothermal hydrogen absorption test, ball-milled MgH2 without adding catalyst can only absorb a small amount of hydrogen at 100°C. Figure 13As shown, ball-milled MgH2 (MgH2) can only absorb 1.9 wt.% of hydrogen within 60 min at 100°C.

[0112] Comparative Example 2

[0113] A method for preparing nickel-manganese-based nanospheres comprises the following steps:

[0114] 0.5 mmol nickel nitrate hexahydrate and 0.25 mmol manganese chloride tetrahydrate were dissolved in 40 mL isopropanol and magnetically stirred for 30 min. Subsequently, 16 ml glycerol was dispersed in the above solution and ultrasonicated for 30 min. The solvent thermal reaction was carried out at 180°C for 10 h. After the reaction, the precipitate was collected by centrifugation and dried, and calcined at 400°C in air atmosphere for 2 h to obtain nickel-manganese-based nanospheres.

[0115] The application of the nickel-manganese-based nanospheres in magnesium hydride hydrogen storage is as follows:

[0116] 0.05g of nickel-manganese-based nanospheres and 0.45g of commercial magnesium hydride were ball-milled at room temperature at a speed of 500r / min for 4h. The resulting composite sample was then subjected to variable temperature hydrogen desorption, isothermal hydrogen desorption, and isothermal hydrogen absorption performance tests. The variable temperature hydrogen desorption test conditions were as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 450°C at a heating rate of 5°C / min. The amount of hydrogen released during this process was measured. The isothermal hydrogen desorption performance test was as follows: 150mg of the composite sample was transferred to a hydrogen storage tester and heated from room temperature to 275°C at a heating rate of 5°C / min. The sample was kept at 275°C for 30min. The amount of hydrogen released during the 275°C holding period was measured and plotted as an isothermal hydrogen desorption curve. The isothermal hydrogen absorption test conditions are as follows: 150 mg of the composite sample was transferred to the hydrogen storage tester, and the temperature was raised from room temperature to 100 °C at a heating rate of 5 °C / min. A hydrogen pressure of 4 MPa was provided at 100 °C and kept warm for 1 h. The amount of hydrogen absorbed during the 100 °C holding process was measured.

[0117] The variable temperature hydrogen release test showed that the magnesium hydride catalytically modified with nickel-manganese-based nanospheres prepared in this comparative example can reduce the hydrogen release temperature, but the modification effect is worse than that of Example 1. After modification with nickel-manganese-based nanospheres, the initial hydrogen release temperature is reduced to 280°C, and hydrogen release can be completed at 352°C. The isothermal hydrogen release test showed that the magnesium hydride catalytically modified with nickel-manganese-based nanospheres prepared in this comparative example can increase the hydrogen release rate, but the modification effect is worse than that of Example 1. After modification with nickel-manganese-based nanospheres, 2.51wt.% of hydrogen can be released within 7 minutes at 275°C, and hydrogen release is completed in 20 minutes. The isothermal hydrogen absorption test showed that the magnesium hydride catalytically modified with nickel-manganese-based nanospheres prepared in this comparative example can increase the hydrogen absorption rate, but the modification effect is worse than that of Example 1. After modification with nickel-manganese-based nanospheres, 2.37wt.% of hydrogen can be absorbed within 5.5 minutes at 100°C, and hydrogen absorption is completed in 64 minutes.

Claims

1. A nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere (NiMnO@NC) composite material, characterized in that: The composite material is a nickel-manganese-based bimetallic nanosphere with a nitrogen-doped carbon layer coated on its surface.

2. The nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere (NiMnO@NC) composite material according to claim 1, characterized in that: The microscopic morphology of the composite material is a nanosphere structure with a particle size of 150-200 nm.

3. The method for preparing the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material according to claim 1 or 2, comprising the steps of: (1) fully dissolving the nickel source and the manganese source in isopropanol, adding glycerol, mixing uniformly, subjecting to solvent thermal reaction, centrifuging, drying, and calcining to obtain nickel-manganese-based nanospheres; (2) The nickel-manganese-based nanospheres are fully dispersed in an alkaline aqueous solution, a dopamine source is added, and the mixture is reacted, centrifuged, washed, dried, and calcined to obtain a nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material.

4. The method for preparing the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material according to claim 3, characterized in that: In step (1), the molar ratio of the manganese source to the nickel source is 1:(1-5), preferably 1:

2.

5. The method for preparing the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material according to claim 3, characterized in that: In step (1), one or more of the following conditions are included: i. The nickel source is one of nickel sulfate, nickel nitrate, nickel chloride or nickel acetate; ii. The manganese source is one of manganese sulfate, manganese chloride, manganese nitrate or manganese acetate; iii. The molar amount of the nickel source and the volume ratio of isopropyl alcohol are 0.01 to 1 mmol / mL, preferably 0.0125 mmol / mL; iv. The volume ratio of glycerol to isopropyl alcohol is 0.1-1:1, preferably 0.4:1; v. The temperature of the solvent thermal reaction is 120-200°C; the time of the solvent thermal reaction is 4-10 hours; vi. The calcination temperature is 400-500°C; the calcination atmosphere is air; and the calcination time is 1-4 hours.

6. The method for preparing the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material according to claim 3, characterized in that: In step (2), one or more of the following conditions are included: i. The pH of the alkaline aqueous solution is 8 to 9; the alkaline aqueous solution is a tris(hydroxymethyl)aminomethane hydrochloride aqueous solution or an ammonia aqueous solution; ii. The mass ratio of the nickel-manganese-based nanospheres to the alkaline aqueous solution is 1:0.5-5 mg / mL; iii. the dopamine source is dopamine or dopamine hydrochloride; iv. The mass ratio of nickel-manganese-based nanospheres to dopamine source is 1:(0.5-2), preferably 1:

1.

7. The method for preparing the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material according to claim 3, characterized in that: In step (2), one or more of the following conditions are included: i. The reaction temperature is room temperature, the reaction time is 12 to 24 hours, and the reaction is carried out under stirring conditions; ii. The calcination temperature is 400-500° C.; the calcination atmosphere is an inert gas; preferably, the inert gas is nitrogen or argon; and the calcination time is 1-4 hours.

8. Use of the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material as claimed in claim 1 or 2 in magnesium hydride hydrogen storage.

9. The use according to claim 8, characterized in that The application method comprises the steps of: uniformly mixing a nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material with magnesium hydride by ball milling to obtain a modified magnesium hydride material for use in magnesium hydride hydrogen storage.

10. The use according to claim 9, characterized in that The mass ratio of the nitrogen-doped carbon-coated nickel-manganese-based bimetallic nanosphere composite material to magnesium hydride is 1:7-22; the ball milling speed is 350-650 r / min, and the ball milling time is 2-5 h.

Citation Information

Patent Citations

  • High-sulfur petroleum coke-based sulfur self-doped mesoporous carbon loaded Fe-TM bimetallic alloy catalyst as well as preparation method and application thereof

    CN119524882A

Cited By

  • Nitrogen-doped carbon modified Ni / MgAlO catalyst as well as preparation method and application thereof

    CN121103410A